Controlled Formation of Porous 2D Lattices from C3‐symmetric Ph6−Me‐Tribenzotriquinacene‐OAc3. Issue 10 (4th January 2023) - Toksabay, Sinem; Leisegang, Markus; Christ, Andreas; Härtl, Patrick; Krebs, Johannes; Marder, Todd B.; Haldar, Soumyajyoti; Heinze, Stefan; Bode, Matthias; Krueger, Anke
Abstract: The on‐surface self‐assembly of molecules to form holey nanographenes is a promising approach to control the properties of the resulting 2D lattice. Usually, planar molecules are utilized to prepare flat, structurally confined molecular layers, with only a few recent examples of warped precursors. However, control of the superstructures is limited thus far. Herein, we report the temperature‐controlled self‐assembly of a bowl‐shaped, acetylated C 3 ‐symmetric hexaphenyltribenzotriquinacene derivative on Cu(111). Combining scanning tunneling microscopy (STM) and density functional theory (DFT) confirms the formation of highly differing arrangements starting with π‐stacked bowl‐to‐bowl dimers at low coverage at room temperature via chiral honeycomb structures, an intermediate trigonal superstructure, followed by a fully carbon‐based, flattened hexagonal superstructure formed by on‐surface deacetylation, which is proposed as a precursor for holey graphene networks with unique defect structures. Abstract : STM investigation of temperature‐controlled deposition of hexaphenyl‐methyltribenzotriquinacene with thermolabile acetate groups revealed highly ordered coverage and temperature dependent self‐assembly of this C 3 symmetric structure. At higher temperature the structure flattens and interacts strongly with the metal substrate due to loss of all acetate groups and the methyl groups resulting in an unsaturated triquinacene core.